Bang Chan Social History of a Rural Community in Thailand - Sharp, Lauriston (Cornell University Press, 2018)
Bang Chan traces the changing cultural characteristics of a small Siamese village during the century and a quarter from its founding as a wilderness settlement outside Bangkok to its absorption into the urban spread of the Thai capital. Rich in ethnographic detail, the book sums up the major findings of a pioneering interdisciplinary research project that began in 1948. Changes in Bang Chan's social organization, technology, economy, governance, education, and religion are portrayed in the context of local and national developments.